Clinical Significance of Circulating Tumor Cells in Gastric Cancer - Hye Kyung Jeon; Gwang Ha Kim (The Korean Journal of Helicobacter and Upper Gastrointestinal Research, 2018)
Cancer specimens obtained via surgical resection or biopsy are generally used to understand tumor-associated alterations; however, those approaches cannot always be performed because of their invasive nature, and they may fail to reflect current tumor dynamics and drug sensitivity, which may change during the therapeutic process. Therefore, many research groups have focused on developing a non-invasive biomarker with the ability to monitor tumor dynamics. Circulating tumor cells (CTCs) are metastatic cells released from the primary tumor into the bloodstream. Hematogenous spreading of CTCs is a crucial step in the metastatic cascade, which leads to the formation of overt metastases. CTCs have attracted considerable attention because of their easy accessibility and their superiority over conventional tumor markers. Detecting CTCs is considered a valuable modality to determine prognosis and monitor response to systemic therapies in patients with gastric cancer. Moreover, molecular analyses of CTCs may provide important biological information for individual patients with cancer, which may lead to the development of personalized cancer treatment. In this article, we review potential roles and clinical applications of CTCs in patients with gastric cancer.